Tratamiento erróneo de la escena del crimen en Ecuador y sus efectos en investigaciones penales, vulneración al debido proceso penal - Falquez Idrovo, Joseantonio (2025)
This investigation is the result of a series of questions concerning to the poor treatment of the crime scene in Ecuador and its consequences in criminal investigation and the law enforcement, transparency, due process and otherfundaments thatmake itup and how this affectsour society with cold casesthroughout history. The crime scene as a physical place is susceptible to all kind of contaminating factors, such as climatic phenomena for example rain, wind or snow, as well through human error. In the same way, social factors like wrong manipulation by curious people that have nothing todowith whathappened............